Kepuasan Pelanggan Sebagai Mediator Hubungan Antara Kualitas Pelayanan dan Loyalitas Pelanggan (Donatur) Pada Baitul Maal Hidayatullah Unit Penghimpunan Perwakilan (BMH UPP) Probolinggo - M. Syarif Hidayatullah Elmas; Yekti Rahajeng; Toni Herminto (Fakultas Ekonomi Universitas Panca Marga, 2016)
This study is aim to determine (1) the influence of service quality on customer satisfactions (volunteer) BMH UPP Probolinggo; (2) influence of service quality to customer loyalty (volunteer) BMH UPP Probolinggo (3) customer satisfaction can be mediator variable relation between service quality to loyalty (volunteer) BMH UPP Probolinggo. The number of populations and samples are 85 respondens. The collectng data are used to distribute of questionaires to customers (volunteer) who got mandate the funds by coming directly to the BMH UPP Probolinggo. The methods of data analysis used multiple linear regression and path analysis and Sobel Test to test influence and mediation relationship between variables.The results are (1) quality of service influence to customer satisfaction; (2) quality of service influence to customer loyalty (volunteer); (3) customer satisfaction becomes the mediator variable between service quality and customer loyalty (volunteer) on BMH UPP Probolinggo. Keywords: service quality, satisfaction, loyalty